1999
DOI: 10.1590/s0103-90161999000200002
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade Do Pólen Em Variedades De Laranja Doce

Abstract: Uma vez que a polinização é um dos pontos decisivos para o crescimento e desenvolvimento do fruto, contribuindo com os gametas masculinos para a fecundação e determinando, na maioria das vezes, a fixação dos frutos em citros, torna-se necessário conhecer o grau de esterilidade masculina nas diferentes variedades de laranja doce para sua possível utilização em programas de melhoramento. A esterilidade é limitante para programas que envolvam a hibridação sexual, por outro lado possui sua importância econômica em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…There are several methods for the evaluation of pollen viability, e.g., evaluation by acetic carmine staining (Domingues et al 1999), incubation in Baker solution (Oliveira et al 2001) or the germination test in culture medium Raseira 2006, Pio et al 2007). The method of assessing the viability of pollen through germination in culture medium in vitro is practical and accurate (Einhardt et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for the evaluation of pollen viability, e.g., evaluation by acetic carmine staining (Domingues et al 1999), incubation in Baker solution (Oliveira et al 2001) or the germination test in culture medium Raseira 2006, Pio et al 2007). The method of assessing the viability of pollen through germination in culture medium in vitro is practical and accurate (Einhardt et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, de acordo com outros autores, esses testes estão associados apenas à detecção de substâncias constituintes dos grãos de pólen, como amido e lipídios, que podem estar presentes tanto em grãos de pólen maduros como nos abortados (King 1960, Beyhaut 1988, Rodriguez-Riano & Dafni 2000. Corantes, como o carmim acético e a solução de Alexander, são também utilizados como indicativos de viabilidade polínica (Mulugeta et al 1994, Domingues et al 1999, Rigamoto & Tyagi 2002, porém para Báez et al (2002) e Pline et al (2002) estes testes refletem somente a integridade de estruturas celulares, como núcleo e membrana plasmática.…”
Section: Introductionunclassified
“…Cavalcante et al (2000) found variances of 9 to 98% in the estimation of the viability of the pollen of tangeleiros, using propionic carmine as dye. Domingues et al (1999) found viability of up to 78.2% in pollen in the 'Common Caipira' variety of oranges. Brugnara et al (2011) reported values varying from 42% to 70% of viability in mandarins (Citrus sp.)…”
Section: Couto (2002)mentioning
confidence: 96%